Entrepreneurship in Context: Exploring the Influencing Factors on Entrepreneurial Activity in Germany - Kumar, Priyanka (2016)
This dissertation explores the influence of the German business environment on entrepreneurial intentions. As such, the key research question underlying this dissertation is ‘To what extent does the German business environment encourage entrepreneurs to create new ventures?’. In order to investigate this, existing literature concerning contextual influences on entrepreneurship have been critically evaluated in terms of institutional features as well as prevailing environmental conditions in Germany. Whilst the contextual influence on entrepreneurial propensities has been scrutinised by scholars, they have largely incorporated transition, developing and developed economies in their research design, however, rarely considered Germany as an empirical focus. In the scope of this dissertation, an interpretive methodology has been undertaken, using semi-structured interviews with nine entrepreneurs, who have established their businesses in Germany. According to the theoretical analysis as well as the empirical evidence, it can be suggested that despite various impediments hampering entrepreneurial activity in Germany, the entrepreneurial environment is changing positively facilitating the actions of entrepreneurs. The dissertation concludes by considering the implications of the findings, which suggest to taking regional peculiarities into consideration.